Optimization principles of rural tourism оrganization : ст. - Terletska, O. V.; Kushnir, L. P.; Martyniuk, U. A.; Perih, T. V.; Bahriy, M. V. (Stepan Gzhytskyi National University of Veterinary Medicine and Biotechnologies, 2023)
The article presents the theoretical substantiation of the optimization principles of the organization of rural tourism development. The urgency of rural tourism development in Ukraine is noted. It is emphasized that today the development of rural tourism is mainly spontaneous, which requires scientifically sound optimization of such activities. Its organizational structure, functional features and problems and prospects of development are shown. The author's interpretation of the concept of "optimization of rural tourism" as a process of organization of relevant tourism activities, which contributes to the provision of these activities the most efficiently, with appropriate unity of its structural components, minimizing resource costs and maximizing emotional and health effects for tourists. The issues of organizational functions are considered. Concerning rural tourism in particular, its organizational function is represented by such a ratio of internal and external organizational factors that ensure the existence of a relevant individual rural facility focused on the provision of tourist services. The structure of rural tourism organizations is analyzed. It should be understood as a set of organizationally integrated forms of activity that are implemented as sustainable processes and aimed at the connection between all organizational components. The unity of organizational structural components of rural tourism becomes the basis for its overall optimization. It should be noted that all organizational structural components of rural tourism are not only interconnected but also interpenetrating, mutually supportive and generally form a single organizational unit, which is a property of tourism-oriented rural systems, aimed at coordinated development of their structured basis. organizational mechanisms. Specific measures to further improve the development of rural tourism in Ukraine are presented.
Keywords: rural tourism; сільський туризм